An Analysis of English Department Students' Difficulties in Answering TOEFL Test of Listening Comprehension - Parni Rina; Yuli Tiarina (Journal of English Language Teaching, 2021)
This study aims to find out the English students’ difficulties in answering TOEFL test of listening comprehension and the factors of the difficulties. The sample of this study was the English department students of Universitas Negeri Padang who have taken the TOEFL test from August to December 2020. They were given 63 questions to explore their difficulties. Descriptive quantitative research is used in this study. The result showed that the English department students were disagree that they face difficulty in answering TOEFL test of listening comprehension. However, they agreed that lack of vocabulary, lack of concentration, length and speed of listening and physical condition were the factors that encountered during the process of answering TOEFL test. By guessing the answer and using clues were the strategies they used to overcome the difficulties in answering TOEFL test of listening comprehension.